KALIMAT DALAM KAIN RENTANG DI KOTA BANDUNG - Saptarini, Tri (Fakultas Komunikasi, Sastra, dan Bahasa, 2017)
Bandung is a city which considered able to combine the landscape beauty, cultural uniqueness, and culinary diversity as its tourism potentials. One of cultural uniqueness of Bandung is banner. In this consideration, Bandung people need to take care the writings on the banners of Bandung so that they follow correct language structures of Indonesian language. The present research analysed the sentences on banners in Bandung and whether they followed the sentence patterns of Indonesian language from a book which titled